1996
DOI: 10.1016/0277-9536(95)00200-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care: A comparison of preferences between medical specialists and patients with chronic diseases

Abstract: the patients and medical specialists researched did not show wide differences of opinion on preferences of care in relation to quality. The only exception to this concerned 'continuity of care' which was ranked higher by patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…These maps can also be used with policy makers and program developers to identify future actions for change. The CM method has been extensively used in planning and evaluation [14] and more recently, in studies related to mental health [19,20], violence [21,22], gambling [23], child welfare [24], youth development [25], tobacco control [26] and health care models [27,28].…”
Section: Methodsmentioning
confidence: 99%
“…These maps can also be used with policy makers and program developers to identify future actions for change. The CM method has been extensively used in planning and evaluation [14] and more recently, in studies related to mental health [19,20], violence [21,22], gambling [23], child welfare [24], youth development [25], tobacco control [26] and health care models [27,28].…”
Section: Methodsmentioning
confidence: 99%
“…25 Patient satisfaction with treatment outcomes, including detectable improvements in HRQoL, may enhance patient compliance with the treatment regimen-an integral factor for achieving optimal control of COPD. [82][83][84][85][86] Therefore, it is essential to provide the patient with a treatment regimen that will encourage good compliance. Clinical studies have shown that the duration of effect of long-acting bronchodilator therapies (Ͼ12 hours), such as formoterol, salmeterol, and tiotropium, 79,87-90 permit a dosing regimen that may improve patient adherence, 46,47 whereas patients are less likely to comply with treatments of shorter durations of effect that require several actuations per day to achieve the recommended daily dose, 6 such as SABAs and short-acting anticholinergic therapies.…”
Section: Discussionmentioning
confidence: 99%
“…This method is useful in generating not only the emergent concepts but also for engaging the participants in appraising the relevance of concepts for future planning or direction [32]. The CM method has been used extensively in planning and evaluation [31], and more recently in health studies including healthcare modeling [33,34]. …”
Section: Methodsmentioning
confidence: 99%